MAPPING THE GEOMORPHOLOGICAL STRUCTURES IN MALUKU SEA: IDENTIFICATION OF POTENTIAL GEOHAZARD USING MULTIBEAM ECHOSOUNDER - Fadilla R. D., Amalia
The eastern part of Indonesia is composed of a complex tectonic plate setting. The prominent tectonic feature is the Banda arc, which consists of trenches, inner volcanic arcs, and outer arc islands (Hamilton, 1979; Spakman and Hall, 2010). These plates are still active and moving microscopically which will cause several geohazard in Maluku. Several potential geohazard sources have also been found, such as earthquake source inferred from seismic and geodetic data of Meilano et al., (2021) and the locations of aftershock determined in a stepwise approach of Sahara et al. Due to the complex setting of tectonic plates, geomorphological analysis is needs to find out more about the conditions of the seabed in the Maluku Sea. To obtain the seafloor geomorphological structures, bathymetric data can be acquired using multibeam echosounder (MBES). Hence, a hydrographic and shallow geophysical survey was launched by the National Research and Innovation Agency (BRIN) through the Widyatama Expedition ‘The Earthquake Mechanism at Maluku Sea’ (EWIN MeGaMal) Expedition from 8 to 28 August 2022 using the R/V Baruna Jaya VIII. The survey employs seabed mapping in the depths of the Maluku Sea which ranges between 500 m – 3000 m using the MBES Elac Seabeam 3050 operates at a 50 KHz sound wave frequency accompanied by Trimble BX992 as global navigation satellite system (GNSS) used for determining the position and the vessel heading. Based on the results of this study, which utilized the morphometry analysis method to identify the marine geomorphology of Ambon through bathymetry data, various geomorphological structures such as gullies, river channels, landslides, and faults were identified in each survey area. Each of these geomorphological features is indicated to have the potential to cause disasters, such as tsunamis caused by landslides in and earthquakes caused by the movement of active faults.